ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU KONSUMEN TERHADAP PERMINTAAN JAGUNG PADA TINGKAT RUMAH TANGGA DI KECAMATAN PASARWAJO KABUPATEN BUTON - Edy, Safrin (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2019)
The purpose of this study was to analyze the factors that influence consumer behavior towards corn demand in households. This research was conducted in Pasarwajo Sub-district of Buton Regency, namely in three villages including Kaongkeongke, Wangguanggu and Warinta villages in September - December 2018. The population in this study were all households in three villages within the subdistrict area. Sampling was taken by a multi-stages cluster random sampling method with a total sample of 108 households. The results of data analysis obtained the F-count value of 13,674 with a significance level at ? = 0.05 (an error rate of 5% or 95% confidence level) of 0,000. The significance value is smaller than the value ? = 0.05, and the coefficient of determination (R2) is 0.525, which means that 52.5% of the diversity of the dependent variable (corn demand) is explained or can be explained by the diversity of independent variables, namely the price of corn, prices rice, cassava prices, household income, number of household members, and housewife education significantly influence the demand for corn, while the price of sweet potatoes and tastes do not significantly affect the demand for corn. The remaining 47.5% is explained by the diversity of other variables not included in the analysis model. Based on the results and discussion, it can be concluded that consumer behavior is influenced by variable corn prices, rice prices, cassava prices, household incomes, number of household members, and housewife education significantly influence corn demand, whereas sweet potato prices and tastes do not significantly influence demand corn.   Keywords: consumer behavior, corn demand, households